Proses Pembelajaran Karawitan Menggunakan Metode Fun teaching di SMP Negeri 12 Semarang - Amelia Rahma Pertiwi; Siti Aesijah (Pusat Riset dan Inovasi Nasional, 2025)
Karawitan is one of the traditional arts native to Indonesia that has high cultural value, but now it is increasingly rare and is starting to be marginalized, especially among the younger generation. In Semarang City, karawitan learning faces various challenges, such as the lack of student interest, the assumption that karawitan is an ancient and boring art, and the limitations of interesting learning methods. Therefore, an innovative approach is needed to regrow students interest in karawitan. This study aims to analyze the improvement of students ability to play gamelan through the application of the Fun teaching method in karawitan learning at SMP Negeri 12 Semarang. The research method used is qualitative descriptive, focusing on the learning process, student responses, and challenges faced during the implementation of learning. The research location was chosen purposively, with 30 subjects from grades VII to IX actively participating in cultural arts subjects, especially karawitan. Data collection is carried out through direct observation in learning activities, interviews with students and teachers, and documentation of learning activities. The results of the study show that the application of the Fun teaching method has succeeded in creating a fun, participatory, and non-monotonous learning atmosphere. Students responded positively to learning activities, feeling more interested and enthusiastic in playing gamelan. Creative activities such as rhythmic games, light competitions, and the incorporation of visual and audio elements have been proven to increase students engagement and understanding of gamelan instruments.